2022
DOI: 10.3390/jcm11247333
|View full text |Cite
|
Sign up to set email alerts
|

Class II Malocclusion in Adult Patients: What Are the Effects of the Intermaxillary Elastics with Clear Aligners? A Retrospective Single Center One-Group Longitudinal Study

Abstract: Aim: To evaluate the dental effects of the treatment with clear aligners and intermaxillary elastics in adult patients with Class II malocclusion. Material and methods: A sample of 20 Class II patients treated with Invisalign aligners (5 M and 15 F; mean age of 27.6 ± 6.3 years) was included in this single-center one-group longitudinal study. Dental cast and cephalometric records were analyzed before (T0) and after treatment (T1). Data were analyzed with a T-test for paired data (p < 0.05). Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In our study, patients were asked to wear elastics bilaterally for 24 h of the day. Often, in clinical settings, Class II elastics are used as anchorage reinforcement and to improve the distalization achieved by the aligners, [21,22] but it is difficult to evaluate how much distalization is due to the aligner and how much is due to the elastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, patients were asked to wear elastics bilaterally for 24 h of the day. Often, in clinical settings, Class II elastics are used as anchorage reinforcement and to improve the distalization achieved by the aligners, [21,22] but it is difficult to evaluate how much distalization is due to the aligner and how much is due to the elastics.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral fixed appliances, such as the pendulum appliance and distal jet [17,18], were introduced as more aesthetically-acceptable alternatives to headgear, since they minimize or eliminate the need for compliance; by using the palate, teeth, or both as sources of anchorage, the main side effect is anterior anchorage loss [19]. Moreover, intermaxillary Class II elastics and other intraoral fixed appliances (Herbst, Forsus) could be used to improve a molar Class II relationship in children and adolescents, but the main outcomes involve dental advancement of the mandibular arch [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Consequentially, they opted for an alternative approach with the extraction of two lower and one upper premolar in order to center the lower dental midline with the upper one and to obtain a molar and canine Class I on the Class I side and a molar Class III and canine Class I relationship on Class III side, with a minimal use of inter-maxillary elastics. Brunetto et al [ 25 ] presented a case of Class III subdivision malocclusion, managed as a non-extractive treatment, with the use of Class III elastics 24 hours per day applied on one side only; however, the long-term use of unilateral inter-maxillary elastics may lead to undesired effects on both arches, such as the extrusion of the teeth involved, resulting in a canting of the occlusal plane [ 27 ]. Zimmer et al [ 26 ] demonstrated that treating Class III malocclusion by the isolated extraction of lower premolars could be a valid alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Clear aligner therapy has become quite popular and nowadays are used to treat various kinds of malocclusion such as Class II, Class III and interdisciplinary cases 1 6 also considering some of their advantages such as greater ease to maintain good gingival health, lower impact on general well-being and less visibility 7 , 8 . However, despite the wide use of aligners, they still present an extreme variability in the movement accuracy 9 .…”
Section: Introductionmentioning
confidence: 99%